The Functions and Mechanisms of Low-Level Laser Therapy in Tendon Repair (Review) - Lyu, Kexin; Liu, Xueli; Jiang, Li; Chen, Yixuan; Lu, Jingwei; Zhu, Bin; Liu, Xinyue; Li, Yujie; Wang, Dingxuan; Li, Sen (Frontiers in Physiology, 2022)
Tendon injury is a common disease of the musculoskeletal system, accounting for roughly 30-40% of sports system disorder injuries. In recent years, its incidence is increasing. Many studies have shown that Low-Level Laser Therapy has a significant effect on tendon repair by firstly activating cytochrome C oxidase and thus carrying out the photon absorption process, secondly acting in all the three phases of tendon repair, and finally improving tendon recovery. The repair mechanisms of LLLT are different in the three phases of tendon repair. In the inflammatory phase, LLLT mainly activates a large number of VEGF and promotes angiogenesis under hypoxia. During the proliferation phase, LLLT increases the amount of collagen type III by promoting the proliferation of fibroblasts. Throughout the remodeling phase, LLLT mainly activates M2 macrophages and down-regulates inflammatory factors, thus reducing inflammatory responses. However, it should also be noted that in the final phase of tendon repair, the use of LLLT causes excessive upregulation of some growth factors, which will lead to tendon fibrosis. In summary, we need to further investigate the functions and mechanisms of LLLT in the treatment of tendon injury and to clarify the nature of LLLT for the treatment of diverse tendon injury diseases.